Volatility spillover effects: Evidence from emerging markets - Vladimirova, Ekaterina (My University, 2018)
The purpose of this study is to provide empirical evidence of volatility spillovers from global and main regional stock markets to a number of emerging markets. The research includes weekly stock market index prices from 2000 to 2018 obtained from DataStream International, and all stock market data is transformed into returns by calculating log differences. There are 956 observations in total. Following developed markets are considered in this paper: the US, aggregate developed European countries, Hong Kong, Japan and Singapore. Also, ten European and Asian emerging markets are included in this research: Czech Republic, Indonesia, Greece, Hungary, Malaysia, the Philippines, Russia, Taiwan, Thailand and Turkey. Researches on volatility spillovers have come back after several financial crises. There are different approaches and methods for volatility spillovers estimation. In this paper, in order to find existence of volatility spillovers, a three-step univariate AR ( 1 )-GARCH ( 1, 1 ) econometric model is applied. The study captures statistically significant volatility spillovers from developed markets to all emerging markets. Also, obtained results show that European emerging markets are more affected by US volatility, and European volatility spillover effects are stronger than Asian spillover effects. Furthermore, this research examines the extent of volatility spillovers from developed stock markets during crisis and non-crisis periods by adding a dummy variable into introduced econometric model. It is observed that during crisis period, US volatility spillovers to emerging markets tend to increase, while volatility spillovers from main regional stock markets decrease. The only exception is Japanese stock market: all five Asian emerging markets experience higher volatility spillovers from Japan during crisis. Also, during financial crisis, Indonesian stock market is affected by increased volatility spillovers from all three developed Asian markets. Additionally, variance ratios are calculated in order to estimate global, regional and pure local effects in conditional variances of individual emerging countries. According to estimated results, regional effect is dominating in conditional variances of emerging markets’ unexpected returns.
Keywords: volatility spillovers; emerging stock markets; crisis transmission; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|